Derivation of canine hepatocyte in vitro models to study Branched-Chain Amino Acid effects on liver functions. (International Journal of Health, Animal Science and Food Safety, 2016)
Branched chain amino acids (BCAA), have been shown to affect human gene expression, proteinmetabolism, apoptosis, and regeneration of hepatocytes. Furthermore, they have been demonstratedto inhibit proliferation of liver cancer cells in vitro, and to be essential for lymphocyte proliferation.In veterinary medicine, the use of BCAAs as integration of a normal dietary plan, is likely to be a validchoice for the same benefit found in human clinical nutrition, although this aspect is still debated.Indeed, long-term oral supplementation with BCAAs in the prevention of liver fibrosis and injury in thedog's liver is still unclear. Aim of the present study will be to determine how BCAAs preserve liverfunctions in vitro. To this purpose we have selected and set up three different in vitro models: hepaticdog cells and canine hepatocellular carcinoma cells plated in 2D monolayer and hepatic dog cellscultured onto 3D scaffolds, obtained from decellularized rabbit liver. All cells adhered and proliferatedonce plated. Cells grown in monolayer quickly entered G0 end arrested growth, ELISA test confirmedtheir ability to produce albumin. Cells grown on scaffold vigorously replicated and showed theircapability to recellularize ECM rabbit liver. These results, although preliminary, demonstrate that theculture conditions used well preserved the original phenotype and function and further support thepossibility to use in vitro models to successfully study BCAA efficacy in dog.
Keywords: Canine Hepatocyte; BCAA; decellularizatio; liver; scaffold